THE INFLUENCE OF MANAGERIAL OWNERSHIP AND CHARACTERISTICS OF THE BOARD OF COMMISSIONERS ON COMPANY PERFORMANCE - Fitri Nurjanah (Jurnal Scientia, 2022)
The purpose of this study was to analyze the effect of managerial ownership and the characteristics of the board of commissioners on company performance. This study uses 212 samples of manufacturing companies listed on the Indonesia Stock Exchange for the period 2018 to 2020. The analysis used in this study is a Multiple Regression analysis model which is processed with SPSS 20 software. This study uses a total sample of 292 companies. The results of this study state that the existence of an independent board of commissioners in the company has a significant positive effect on firm value. The second hypothesis states that managerial ownership has a significant positive effect on company performance.